2022
DOI: 10.1021/acs.jafc.2c08351
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Attenuates Di(2-ethylhexyl) Phthalate-Induced Mitochondrial Damage and Inflammation in Kidney via cGAS–STING Signaling

Abstract: Di(2-ethylhexyl) phthalate (DEHP) is a highly harmful and persistent environmental pollutant. Due to its unique chemical composition, it frequently dissolves and enters the environment to endanger human and animal health. Lycopene is a natural bioactive component that can potentially reduce the risk of environmental factor-induced chronic diseases. The present study sought to explore the role and underlying mechanism of lycopene (LYC) on DEHP-induced renal inflammatory response and apoptosis. In this study, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…12,39 Our findings suggest that exposure to ATR leads to interstitial hemorrhage and inflammatory infiltration near the glomeruli and enlarges the cystic lumen to 3.41 and 5.83 times the original size in the A50 and A200 groups, respectively. Previous studies have shown that LYC attenuates renal cortical injury, inflammatory cell infiltration, 40 and apoptosis, 41 and our results suggested that LYC alleviated ATR-induced interstitial hemorrhage and inflammatory infiltration and reduced the enlarged capsular lumen by 26 and 45%, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…12,39 Our findings suggest that exposure to ATR leads to interstitial hemorrhage and inflammatory infiltration near the glomeruli and enlarges the cystic lumen to 3.41 and 5.83 times the original size in the A50 and A200 groups, respectively. Previous studies have shown that LYC attenuates renal cortical injury, inflammatory cell infiltration, 40 and apoptosis, 41 and our results suggested that LYC alleviated ATR-induced interstitial hemorrhage and inflammatory infiltration and reduced the enlarged capsular lumen by 26 and 45%, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Then, IRF7 enters the nucleus and activates the innate immune response ( Barrera et al, 2021 ; Lv et al, 2023 ). A previous study demonstrated that lycopene alleviates renal mitochondrial injury and inflammation induced by plasticizers through the cGAS-STING signaling pathway ( Li et al, 2023 ). Moreover, a study on necrotic enteritis in poultry has shown that dietary chlorogenic acid supplementation can prevent gut inflammation and damage by inhibiting the mtDNA-mediated cGAS-STING signaling pathway ( Lv et al, 2023 ), which supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was reverse-transcribed into complementary DNA (cDNA) using a commercial kit (Thermo Fisher Scientific, Waltham, MA, USA) and a T100 (Bio-Rad, Hercules, CA, USA) thermocycler. The mRNA levels in the colon were detected by GoScript Reverse Transcription System (Promega Biotech, Beijing, China) on a CFX 96 real-time system instrument (Bio-Rad, Hercules, CA, USA) with the following amplification program: 95 °C 120 s and 45 cycles of 95 °C for 5 s, 64 °C for 30 s and 72 °C for 30 s using specific primers ( Table S2 ) [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The housekeeping gene beta-actin was used to standardize the gene expression, and the relative expression level of each gene was calculated using the 2 −ΔΔCT method [ 31 ].…”
Section: Methodsmentioning
confidence: 99%